(3GdYbO GdePgH aj WHbGJ GdePgH (B[ (3ePgH GdEeGe eMeO GdTGaYi (B]s - (3YeQ Hf Ydj Hf CMeO GdCfUGQj GdTGaYj, SQGL GdOjf, CHh MaU GHf GdfMhj, GdeYQha HGHf Gdedbf, J (B804 (3g` s ((3GdbGgQI s)
(3ChdgG (B:s
(3GdMeO ddg hHYO agPg LedI egeI fGaYI Ef TGA Gddg JYGdi ai eYQaI WHbGJ GdTGaYjI jLH Ydi Gdabjg JMUjdgG s
(3BNQgG (B:s
(3hOaf HebHQI GdUhajI NGQL HGH GdfUQ JeJ WHbGJ GdSGOI GdYdeGA GdTGaYjI s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI KGfjI s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs